Natural selection of mitochondria during somatic lifetime promotes healthy aging - Rodell, Anders B.; Rasmussen, Lene J.; Bergersen, Linda H.; Singh, Keshav K.; Gjedde, Albert (Frontiers in Neuroenergetics, 2013)
Stimulation of mitochondrial biogenesis during life-time challenges both eliminates disadvantageous properties and drives adaptive selection of advantageous phenotypic variations. Intermittent fission and fusion of mitochondria provide specific targets for health promotion by brief temporal stressors, interspersed with periods of recovery and biogenesis. For mitochondria, the mechanisms of selection, variability, and heritability, are complicated by interaction of two independent genomes, including the multiple copies of DNA in each mitochondrion, as well as the shared nuclear genome of each cell. The mechanisms of stress-induced fission, followed by recovery-induced fusion and biogenesis, drive the improvement of mitochondrial functions, not only as directed by genotypic variations, but also as enabled by phenotypic diversity. Selective adaptation may explain unresolved aspects of aging, including the health effects of exercise, hypoxic and poisonous preconditioning, and tissue-specific mitochondrial differences. We propose that intermittent purposeful enhancement of mitochondrial biogenesis by stressful episodes with subsequent recovery paradoxically promotes adaptive mitochondrial health and continued healthy aging.